PROTOTYPE DESIGN OF MICRO HYDRO USING TURBINE ARCHIMEDES SCREW FOR SIMULATION OF HIDROPOWER PRACTICAL OF ELECTRO ENGINEERING STUDENTS - Weking, Antonius Ibi; Sudarmojo, Yanu Prapto (Journal of Electrical, Electronics and Informatics; Vol 3 No 1 (2019): JEEI (February 2019), 2019)
Development of new and renewable energy source always developed by world researchers which one of those is energy source from water, because it’s friendly for environment and low cost. Water is one of energy source which it’s have big potential in all Indonesian territory. The main problem from microhydropower plants is a water discharge which it’s flow is not continued every year because influenced by weather season. Micro Hydro is a microhydro power plants (MHP)in a small scale. A micro hydro can be operated in a certain of time if it has a enough water supply. To knowing a right of micro hydro’s  characteristic is not easy thing to learn it. It is because a characteristic each of micro hydro’s installation location is considered specific location.               One type of micro hydro is using Archimedes Screw Turbine. Udayana University of Electrical Engineering Department in this time not have a facility for hydropower field to use this model, so a college student not yet to receive a knowledge of this. Through this research, a writer want to expand a college student’s knowledge in hydropower field with create a prototype of micro hydro with Archimedes Screw Turbine to hydropower practical in laboratory. In this research the effect of screw’s height angle conversion and effect of water pressure conversion has to be researched. In this study will discuss the influence of water pressure and slope of the altitude angle on the rotation produced by the Archimedes screw turbine so that it can be seen the voltage, current, power generated by the generator, torque and efficiency . The result of from handmade equipment for this research in angle 40 0 with biggest generator round (rpm) is 3768 (rpm) and highest power is 10.92057 watt, torque adalah 0.60 Nm dan efisiensi sebesar 14 %. The torque which resulted from water pressure 24 psi is 0,73 Nm and efficience 18,01 %. The voltage, current, and output power which resulted in generator is 85,8 Volt, 0,1963 Ampere and 16,85 Watt. For generator speed round in the pressure 24 Psi is 4582 rpm, while turbine speed round which resulted from the pressure 24 Psi is 383 rpm before coupled with generator and 222 rpm after coupled with generator.